2004
DOI: 10.1016/j.otohns.2003.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Which is Important in the Evaluation of Metastatic Lymph Nodes in Head and Neck Cancer: Palpation, Ultrasonography, or Computed Tomography?

Abstract: Statistical analysis was done with chi(2) test. The difference between histologic findings and palpation is significant (P = 0.0005). The difference between histologic findings and USG and CT is significant (P = 0.0001 and P = 0.0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
1
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 14 publications
7
82
1
8
Order By: Relevance
“…It has disadvantages of being expensive and with hazards of radiation exposure [11,12]. Ultrasound scanning has improved the overall accuracy of diagnosis of cervical metastases [13]. It is a cheap and highly reliable method without hazards of radiation exposure [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has disadvantages of being expensive and with hazards of radiation exposure [11,12]. Ultrasound scanning has improved the overall accuracy of diagnosis of cervical metastases [13]. It is a cheap and highly reliable method without hazards of radiation exposure [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] There was a mix of methodological designs including Randomized Control Trials; [20] correlation studies; [21][22][23][24] mixed methods; [25] and prospective study design. [23] The sample size across the included studies ranged from 13 [18] to 152. [19] Participants were patients, medical/chiropractor students and clinicians (surgeon, dermatology).…”
Section: Reporting Resultsmentioning
confidence: 99%
“…With continued advances in technology, Alderson et al [21] advocated for physicians to rely more on ultrasound when detecting cancer in the head and neck regions as opposed to palpation alone. Similarly, Haberal et al [23] argued that while palpation is a valuable skill, CT paired with ultrasonography (USG) provided accurate and reliable results when combined together. Hoang et al [30] advocated for a systematic approach in assessing the cervical lymph nodes highlighting the use of CT and MRI, while de-emphasizing the need for palpation as smaller nodes can harbor metastases and can be difficult to palpate (p. 17).…”
Section: A Cartesian Perspective On Palpation Knowledgementioning
confidence: 99%
“…The results of the study were in accordance with those reported by Millesi et al [28] and Hodder et al [29], who found values over 90 %. Other authors obtained different results; Haberal et al [30] and Anand et al [31] found rates over 70 %, but Hohlweg-Majert et al [32] described a sensitivity of 24.5 % for US.…”
Section: Discussionmentioning
confidence: 95%